2017
DOI: 10.1016/j.laa.2016.09.027
|View full text |Cite
|
Sign up to set email alerts
|

On the dimension of the algebra generated by two positive semi-commuting matrices

Abstract: Gerstenhaber's theorem states that the dimension of the unital algebra generated by two commuting n × n matrices is at most n. We study the analog of this question for positive matrices with a positive commutator. We show that the dimension of the unital algebra generated by the matrices is at most n(n+1) 2 and that this bound can be attained. We also consider the corresponding question if one of the matrices is a permutation or a companion matrix or both of them are idempotents. In these cases, the upper boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…4.7). Moreover, the paper [6] provides a nontrivial example showing that this upper bound can be attained. In our paper this result is proved in more transparent way that also gives some insight in constructing the just-mentioned example.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…4.7). Moreover, the paper [6] provides a nontrivial example showing that this upper bound can be attained. In our paper this result is proved in more transparent way that also gives some insight in constructing the just-mentioned example.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Kandić andŠivic [6] have studied order analogs of Gerstenhaber's theorem stating that the dimension of the unital algebra generated by two commuting n × n matrices is at most n. They showed that the dimension of the unital algebra generated by two positive n × n matrices A and B is at most n(n + 1)/2 provided its commutator [A, B] = AB − BA is also positive (see Theorem 3.1). Here positivity of a matrix means that it has nonnegative entries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations